Fracture of laser-based powder bed fusion produced Ti6Al4V - Louw, Daniel Francois (Stellenbosch : Stellenbosch University, 2025)
Louw, D. F. 2025. Fracture of laser-based powder bed fusion produced Ti6Al4V. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/961bff00-ca87-4973-8bb3-2f4c7dac059b